Incidence of two leaf fungal diseases in two plum training systems - Molnár, B.; Varga, M.; Vámos, A.; Holb, I. J. (International Journal of Horticultural Science, 2018)
In a two-year study, we aimed to determine the susceptibility of four plum cultivars to two fungal pathogens of plum (Stigmina carpophila and Polystigma rubrum) in two training systems with tree spacings of 4 x 1.5m and 6 x 3m. Results showed that shothole symptoms were not detected on cvs ’Bluefre’ and ’Stanley’ in August, 2016. Disease incidence was above 50% in the case of ’Čačanska lepotica’ in both training systems in 2016. There were no significant difference between the two training systems. Shot hole incidence was lower in the 6 x 3m spacings compared to the 4 x 1.5m spacings on cv ’President’ in 2016. Cultivar ’Čačanska lepotica’ showed the highest incidence of Stigmina carpophila in the 4 x 1.5m spacing in 2017. Disease incidence of Stigmina carpophila was significantly lower in the 6 x 3m spacing compared to the 4 x 1.5m spacing. Shothole incidences on cv ’President’ were similar to the values in 2016 ranging from 40% to 60%. Leaf disease incidence was higher in the 4 x 1.5m spacing compared to the 6 x 3m plot. Low disease incidence (below 10%) was observed on cv ’Stanley’ in 2017 and only in the 4 x 1.5m spacing. There were no visible symptoms of blackhorn dotty in 2016 due to inadequate weather conditions for the Polystigma rubrum fungus. However, all the four cultivars were infected by Polystigma rubrum in 2017. The most susceptible cultivar was cv ’Čačanska lepotica’ with the highest disease incidence in the 4 x 1.5m spacing. Disease incidence of this cultivar was lower in the 6 x 3m spacing which was significantly less than in the 4 x 1.5m spacing. The least susceptible cultivar was ’Bluefre’ and symptoms were observed only in the spacing of 4 x 1.5m. The disease incidence of cv ’President’ was similarly low to cv ’Stanley’ in both spacings.